Using Social Media as a Survey Recruitment Strategy for Post-Secondary Students During the COVID-19 Pandemic - Simran Purewal; Paola Ardiles; Erica Di Ruggiero; John Vincent L. Flores; Sana Mahmood; Hussein Elhagehassan (SAGE Publishing, 2021)
The COVID-19 pandemic rapidly forced Canadian post-secondary students into remote learning methods, with potential implications on their academic success and health. In recent years, the use of social media to promote research participation and as a strategy for communicating health messages has become increasingly popular. To better understand how the pandemic has impacted this population, we used social media platforms to recruit students to participate in a national bilingual COVID-19 Health Literacy Survey. The purpose of the survey was to assess the health literacy levels and online information-seeking behaviors of post-secondary students in relation to the coronavirus. This paper outlines the social media recruitment strategies used for promoting participation in the survey among Canadian post-secondary students during the pandemic. Facebook, Twitter, and Instagram accounts were created to promote the online survey. The objective of this paper is to examine the use of Instagram, Facebook, and Twitter as survey recruitment strategies tailored to students. Data analytics from these platforms were analyzed using descriptive statistics. We found that the most commonly used platform for survey dissemination was Twitter, with 64800 total impressions recorded over 3 months. The use of social media as a survey recruitment strategy showed promise in the current context of COVID-19 where many students are participating in online learning and for a study population that actively uses these platforms to seek out information.